STUDI KELAYAKAN PENDIRIAN PABRIK PAKAN TERNAK AYAM RAS PETELUR DI KOTA PAYAKUMBUH - Hidayatullah, Muhammad Royyan; Harahap, Azwar; Indrawati, Toti (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2017)
This study aims to look at the feasibility of establishing feed mills chicken laying in Payakumbuh terms of marketing, the supply of raw materials, economic and social side of the financial side. This research was conducted in Payakumbuh the object of research is laying chicken breeders in Payakumbuh. Data were analyzed with descriptive analysis to look at the feasibility of animal feed mill in terms of marketing, in terms of raw material supply, in terms of socio-economic and quantitative data analysis to look at the feasibility of animal feed mill in terms of financial, namely using analysis of the Net Present Value (NPV), Ratio Benefits Cost (Cost Benefit Ratio), Internal Rate of Return (IRR). Results of research conducted on 37 respondents note that the feasibility of fodder plant of aspects of the market and the marketing of fodder plant laying chicken included in the category of decent, from the aspect of raw materials establishment of feed mills chicken laying in Payakumbuh feasible to set, from the social aspect economic feed mill laying chicken in Payakumbuh worthy to open and generate profits, fodder plant feasibility of financial aspect rESULTS Net Present Value (NPV) of Rp. 15.490214 billion. Therefore NPV is greater than zero, then laying chicken factory feasible to set. Value Benefit Cost Ratio (B / C ratio) is 1.03, because the B / C ratio is greater than one, then laying chicken factory feasible to set. Value Internal Rate of Return (IRR) is 32.4%. Because this value is greater than the prime interest rate used is 6.5% then laying chicken factory feasible to set in Payakumbuh.Keywords: Feasibility Establishment of Plant and Animal Feed Broiler Laying